L. A. outlaws : [large type] : a novel - Parker, T. Jefferson (Parker, T. Jefferson. Charlie Hood novel., 2008)
Investigating the latest crime scene of a celebrity thief who has been staging lucrative heists and donating the spoils to charity, rookie deputy Charlie Hood is forced to make an ethics-testing decision when the thief is targeted by a professional killer.